Sodium metabisulphite as a scavenger of air pollutants for wood-based building materials. (November 2013) - Costa, N A; Pereira, J; Ferra, J; Cruz, P; Martins, J; Magalhães, F D; Mendes, A; Carvalho, L H
Abstract : This paper reports on different applications of sodium metabisulphite as a formaldehyde scavenger. The reduction in formaldehyde emission and the effect on physicomechanical properties of particleboards were studied. The scavenger was mixed with urea–formaldehyde resins with different formaldehyde to urea molar ratios and added separately in the production of particleboards. Several differences between the formaldehyde content and physicomechanical properties of boards were found. When applied to melamine–formaldehyde resins, the changes in formaldehyde emission were less significant, probably due to the incorporation of sodium bisulphite in polymeric matrix. The type of formaldehyde-based resin and the form of scavenger addition are the major factors affecting formaldehyde scavenging efficiency.